Assessment of Haemoglobin Polymorphism as a Potential Protein Marker in Selection for Genetic Improvement of the West African Dwarf Goat Population in Nigeria - D.S, Gwaza; H.O, Ukwu; P.A, Ogbole (The International Journal of Biotechnology, 2019)
This study was conducted to ascertain the level of genetic diversity at the haemoglobin (Hb) locus and to assess its potential as a protein marker-assisted selection for genetic improvement of Nigerian West African Dwarf goat populations. Haemoglobin genotyping was performed on forty (40) West African Dwarf goat obtained from Okpokuu local government area of Benue state, Nigeria, using cellulose acetate electrophoresis. Data on Haemoglobin genotypes were also subjected to chi-square test. Two co-dominant haemoglobin alleles HbA and HbB observed controlled three haemoglobin genotypes (HbAA, HbAB and HbBB). The genotypic frequencies were Hb AA 0.42, HbAB 0.50 and HbBB 0.08 for does populations, while that in the bucks population were HbAA 0.38, HbAB 0.44 and HbBB 0.19 respectively. The most frequent haemoglobin genotype observed in the study was HbAB. The heamoglobin genes (allelic) frequencies observed in this study were 0.64 and 0.36 for HbB and HbA respectively. The result of chi-square test was not significant (P>0.05), critical value was 3.84 at 1degree of freedom. Which implies that the oberseved and the expected genotypic frequencies at the heamoglobin locus in west African dwarf goat populations in okpokwu local government area were in handy-Weinberg proportion. Since protein molecules are easily accesseble through electrophoresis, heamoglobin blood protein polymorphism can be used as a potential biochemical marker in selection for genetic improvement of the West African Dwarf goat populations among rural farming communities in Nigeria.